PERTIMBANGAN HAKIM ATAS PENYELESAIAN SENGKETA PAJAK WAJIB PAJAK ORANG PRIBADI YANG DITETAPKAN SEBAGAI PENGUSAHA KENA PAJAK SECARA JABATAN - Kusumo, Vonny Kristanti; Rasji (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Taxpayers whose income exceeds IDR 4.8 billion a year must submit an application to be confirmed as a Taxable Entrepreneur (PKP). If you do not apply on your own behalf, the Fiskus has the authority to determine it ex officio. When confirmed in office, the Fiskus will examine the Taxpayer and determine the tax debt and sanctions. The result of the tax audit is a Tax Underpayment Assessment Letter (SKPKB). The results of the examination can give rise to disputes due to differences in the desires and interests of the two parties, namely the WP and the Fiskus. Tax dispute resolution can be carried out from the stages of impure, pure and extraordinary legal efforts. In a pure and extraordinary legal effort, the Panel of Judges is tasked with examining and deciding the tax dispute with considerations as the basis for producing a fair decision. This research will discuss the judge's perspective on resolving tax disputes for Individual Taxpayers who are designated as Taxable Entrepreneurs in their decisions based on case studies in Supreme Court Decision No.4686/B/PK/Pjk/2022. This research is normative research with a legislative approach that uses secondary data in the form of primary legal materials, namely statutory regulations, Tax Court decisions and Supreme Court decisions and secondary legal materials, namely journals, legal books, articles and others.